Perceived Stress among Students in Medical/Dental and Allied Health Universities in Pakistan due to COVID-19 Pandemic - Asad Tamizuddin Nizami, Mehwish Anwar, Aalia Akhtar Hayat, Fakiha Shabbir, Abdul Moizz Asad Nizami, Muhammad Umar, Asad Tamizuddin Nizami, Mehwish Anwar, Aalia Akhtar Hayat, Fakiha Shabbir, Abdul Moizz Asad Nizami, Muhammad Umar (Journal of Rawalpindi Medical College, 2021)
Objective: Aim of the study was to explore the perceived stress in students at various medical and dental universities across Pakistan during the COVID 19 pandemic, using a validated scale. Materials and Methods: The study took place at the Institute of Psychiatry (IOP) Rawalpindi Medical University (RMU). Results: About 400 medical students participated countrywide. The final analysis was conducted on 333 participants who completed the survey form. Study participants comprised 69.1% female and 30.9% male students. About 74.5% of the participants represented Punjab province, 1.2% were from Sindh, another 1.2% belonged to Baluchistan, 2.4% were from KPK, and 1.5% were from AJK while 19.2% of them resided in Islamabad. The majority of participants were enrolled in MBBS (78.4%) while the rest were from BDS (3%), Allied Health Sciences (12.9%), Clinical Psychology (3.6%), and Pharm D (2.1%). The mean perceived stress score was 21.34, SD=4.90 suggesting high perceived stress levels. Approximately 4.5% of students perceived low levels of stress, 80.2% perceived moderate stress, whereas 15.3% scored high on the perceived stress scale. Male students had statistically significant (p=0.38) lower stress levels (M=19.99, SD=5.91) as compared to females (M= 21.95, SD= 4.26). Conclusions: Perceived stress level in medical students was alarmingly high and requires urgent intervention by the Medical and Dental Universities for immediate action and policy guidance for early identification and effective management. This can be achieved by delivering targeted e-workshops and evidence-based e-trainings for stress management like psychological first aid and mindfulness techniques.